Promoting Teaching Academic Writing Among German Teacher Candidates in Turkey in the Sample of Abstract Text Writing - An Action Research - HEPPINAR, GÜLAY (ISTANBUL UNIV, FAC LETTERS, 2019)
The processing of the information read is a big challenge for the students. The abstract text takes an important function to overcome this challenge. This is because the abstract text mediates the transformation of expert knowledge into individual information in the way of reproducing the text. Thus, the summarization is one of the main achievements of German teacher candidates and has impact not only on their success in university, but also on their future working lives. The aim of this study is to develop a model for writing an abstract text for the students in the Department of German Language Teaching and to represent the results in relation with this model. For this purpose, an action research based on written questionnaire and using quantitative data collection tools has been carried out. The sample group of the study consists of 22 2nd grade students in total attending the Department of German Language Teaching at Marmara University. After the model has been applied for a 6-week period, a written questionnaire about the texts used in the model, the teaching method, the activities used in the model, the proceedings obtained through the model and the general results related to the model aiming to write an abstract text has been conducted with the students during evaluation stage. According to the data regarding to the self-assessments of the students, thanks to the model about teaching how to write a academic text in the sample of abstract text writing, the students have made progress in expressing the author's action, specifying the argumentative structure, connecting the sentences and using appropriate conjunctions.
Keywords: Academic writing; abstract writing; German as a foreign language; foreign language teaching; action research